New Provisions Concerning Animal Experiments. The Most Important Changes and an Attempt of Assessment - Smykowski, Krzysztof (Studia Ecologiae et Bioethicae, 2017)
Act of 15 January 2015 on the protection of animals used for scientific and educational purposes implemented Directive of the European Parliament and of the Council of 22 September 2010 on the protection of animals used for scientific purposes. The above legal acts have led to a number of changes concerning the conduct of scientific research with the use of animals. New definitions of the procedure and experiments were formed. Moreover, the range of species subject to protection was expanded by cephalopods and fetal forms of mammals. A completely new scale of invasiveness was implemented. The changes also affected regulatory bodies, namely, the National Ethics Committee for Animal Experiments as well as local ethics committees The majority of new provisions should be accepted with satisfaction because they constitute enforcement of the right proposals concerning the protection of test animals.